2000
DOI: 10.1007/s005350070089
|View full text |Cite
|
Sign up to set email alerts
|

Multicentric hepatocellular carcinomas tend to grow in more damaged segments of the liver

Abstract: In 115 patients (68 with liver cirrhosis and 47 without) who underwent curative resection of hepatocellular carcinoma (HCC) caused by hepatitis C virus (HCV)-related chronic liver diseases, we separated the liver into three segments (right, middle, and left) according to the three secondary branches of the Glissonean pedicle. We examined the weight of each resected segment. We also examined the histological findings of the segments in the same liver in 24 other patients with HCV-related chronic liver diseases.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
3
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 18 publications
1
11
3
1
Order By: Relevance
“…VEGF can substantially accelerate division and growth of vascular endothelial cells and angiogenesis. High VEGF levels can promote plasma protein exosmosis to induce fibrin deposition and new vessel generation, allowing invasion and metastasis; patients with HCC and higher VEFG expression in serum and HCC tissue have a poorer prognosis [9,26]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VEGF can substantially accelerate division and growth of vascular endothelial cells and angiogenesis. High VEGF levels can promote plasma protein exosmosis to induce fibrin deposition and new vessel generation, allowing invasion and metastasis; patients with HCC and higher VEFG expression in serum and HCC tissue have a poorer prognosis [9,26]. …”
Section: Discussionmentioning
confidence: 99%
“…Chronic hepatitis B virus (HBV) and hepatitis C virus (HCV) infections induce approximately 75–80% of HCC in the world [9]. Chronic HBV infection accounts for about 60% of the total liver cancer in developing countries and about 23% of the cancer in developed countries.…”
Section: Introductionmentioning
confidence: 99%
“…Multinodular HCCs in cirrhotic livers most commonly represent multicentric HCCs, whilst multinodular HCCs in non-cirrhotic liver are often related to intraheptic metastases [3]. Multicentric HCCs are particularly common in patients with chronic hepatitis C and tend to grow in more damaged segments of the liver [4,5]. The color of the cut surface may be green (due to bile production), yellow (due to fatty change), tan-brown, or grey-white ( fig.…”
Section: Pathologymentioning
confidence: 99%
“…For resectable cases of HCC, the most patients have a good liver function in preoperation, whereas the late recurrence or death only associated with Child stage in this study, which suggest that liver function damage is the one of reasons which result in late death(no-tumor factors) beside early operative mortality or easy to recurrence. Ariizumi et al [52] showed that multicentric HCC tended to grow in more damaged segments of the liver. Thus, influence of tumor-related factors to patients who survived more than three years with no recurrence decreased gradually, meanwhile the influence of host-related factors, including liver functional status and multicentric in origin increased gradually [18,32] .…”
Section: Discussionmentioning
confidence: 99%